3세 미만 유아를 둔 도시 어머니의 양육 스트레스와 가족기능 - 박영숙(Young Sook Park); Kanzaki Mitsuko(Mitsuko Kanzaki); 박연환(Yeon-Hwan Park); 김윤미(Yunmi Kim) (Seuteureseu yeon-gu (Online), 2009)
본 연구의 목적은 도시에 거주하는 3세 미만의 유아를 둔 어머니의 양육스트레스와 가족기능간의 관련성을 확인하는 것이었다. 2008년 251명의 3세 미만 유아를 둔 어머니를 편의표출하여 양육스트레스는 Parenting stress index (Abidin, 1990)로, 가족기능은 한국형 가족기능 측정도구(Lee IS et al., 2002)로 측정하였다. 연구결과 응답자의 85.3%가 핵가족이었으며, 43.3%의 어머니가 취업모이었다. 어머니의 양육스트레스는 1~5점의 점수범위에서 평균 2.4점으로 중간 수준이었고 부모 영역의 양육스트레스가 아동영역의 양육스트레스 보다 높았다. 가족기능은 1∼4점의 점수범위에서 평균 3.1점의 중상 수준이었고 정의적 결속의 가족기능이 가장 높았고, 다음은 의사소통, 외적자원과 관계의 순이었다. 어머니의 양육스트레스는 어머니의 취업 여부(p＜.001), 배우자 외 양육 도우미 유무(p＜.001)에 따라 통계적으로 유의한 차이를 보였다. 가족기능은 어머니의 나이(p＜.05), 아버지의 나이(p＜.05)에 따른 차이가 통계적으로 유의하였다. 양육스트레스와 가족기능은 통계적으로 유의한 역 상관관계를 보였다(r=−.36, p＜.001). 결론적으로 가족기능을 강화하는 가족중심적인 간호중재를 개발하여 취업모의 양육스트레스를 경감시키는 방안 마련이 필요하다. The aim of this study was to identify the parenting stress, the family functioning and their relationship in mothers with a child below 3 years. We recruited participants (n=251) who had a child less than 3 years of age and lived in urban area randomly in 2008. They completed questionnaire which constructed with Parenting Stress Index (PSI) (78 items) and Korean Family Functioning Scale (24 items). 85.3% of mothers were in nuclear family, 43.4% of mothers had full-time job. The mean score of parenting stress was 2.4 (moderate), and that of family functioning was 3.1 (moderate-high). There were statistically significant differences in the parenting stress by the employment status of mothers (p＜.001), having helper except spouse (p＜001). There were statistically significant differences in the family functioning by the age of mother (p＜.05), the age of father (p＜05). There was a moderate significant correlation between parenting stress and family functioning(r=−.36, p＜0.001). Findings indicate significant correlation between family functioning and parenting stress and suggest possibility of reducing mother's parenting stress by family centered nursing interventions to strengthen family functioning. (Korean J Str Res 2009;17:349∼357) KCI Citation Count: 20